Sunset Bake / Muhamad Afiq Ahamed Siddeekh ... [et al.] - Ahamed Siddeekh, Muhamad Afiq; Mohd Razib, Anis Nabilah; Jamaluddin, Mohammad Nasrul Fadzley; Azmanuddin, Nur Amani Zakirah (2021)
We have been asked to create a partnership business from scratch which then we came up with Sunset Bake company. After the authorization of Sunset Bake for my business plan. We would be able to explain our business ownership, marketing, financial and product/service. Sunset Bake was founded by Anis Nabilah, Muhamad Afiq, Nasrul Fadzley, and Amani Zakirah with the partnership ownership type. The product that they serve in the industry in healthy based food. As well as their main target customer is on dietary people and who want to get food that is healthier. Besides, they are also well-known in the local market because of their flourless brownie which just needs 3 main ingredients as their secret recipe. Unfortunately, there are some problems in the company for customer demands of various types of brownies and cookies. Somehow, Sunset Bake will come out with other future products to get various types of brownies and cookies. Meanwhile, we also try our best to reduce our waste in manufacturing and make people more love in munch and bite our healthy based food. Last but not least, our food is also a good option for keto, paleo, vegan, gluten free and low carb